Examining the Determinants of Ecological Footprint in ASEAN-5 Countries - Ashari, Nesha Rizky; Utama, Muhammad Budi; W., Irwan (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2024)
This study focuses on the ecological footprint as a crucial indicator for assessing the environmental impact of human activities, particularly in the manufacturing sector, household consumption, and agriculture in five ASEAN countries (Indonesia, Malaysia, Singapore, Thailand, and the Philippines). The novelty of this study lies in the empirical analysis of the relationship between the ecological footprint and major sectors in ASEAN countries using panel data for 22 years (2000–2022). This study uses panel data regression with moderating variables to test the interaction between independent variables and the ecological footprint. The findings indicate that the manufacturing sector has a significant effect on the ecological footprint. The manufacturing sector can reduce its ecological footprint by implementing energy efficiency technologies and using environmentally friendly raw materials. Meanwhile, household consumption does not have a direct effect, but under specific circumstances, it can affect the ecological footprint, particularly the consumption of goods or services that excessively utilize natural resources and are not readily recyclable. The agricultural sector tends to increase its ecological footprint due to inappropriate practices, such as forest burning for agricultural expansion. The conversion of natural land to agricultural land also increases the levels of hazardous substances such as nitrogen and phosphorus in the soil, which have a significant impact on the ecosystem. The findings of this study provide new insights into effective governance strategies to support sustainable development. This study demonstrates that governance plays a major role in managing ecological footprints, emphasizing the significance of government intervention. The implication of this study is the need for policies that support environmentally friendly practices to reduce ecological footprints in the ASEAN-5 countries.